Prospective evaluation of the effect of deferasirox on hematologic response in transfusion‐dependent patients with low‐risk MDS and iron overload. (22nd June 2018) - Rose, Christian; Lenoir, Caroline; Gyan, Emmanuel; Hacini, Maya; Amé, Shanti; Corront, Bernadette; Beyne‐Rauzy, Odile; Adiko, Didier; Loppinet, Elena; Ali‐Ammar, Nadia; Laribi, Kamel; Wattel, Eric; et al.
Abstract: Objectives: To assess the reduction of transfusions rate in transfusion‐dependent patients with low‐risk myelodysplastic syndrome (MDS) with iron overload treated with deferasirox. Methods: Prospective observational study. Primary endpoint was reduction in transfusion requirements (RTR) at 3 months, (assessed on 8‐week period). Secondary endpoints were hematologic improvement according to International Working Group (IWG) 2006 criteria at 3, 6, and 12 months. Results: Fifty‐seven patients were evaluable. After 3 months of chelation, no effect was seen on transfusion requirement (5.9 packed red blood cells (PRBC) vs 5.8 before chelation). According to the Kaplan‐Meier analysis, the probability of RTR at 3, 6, and 12 months was assessed as 3.5%, 9.1%, and 18.7%, respectively. Median duration of RTR was 182 days. However, during the 12‐month follow‐up after deferasirox initiation, 17 patients (31.5%) achieved minor erythroid response [HI‐E] according to IWG criteria, 10 of whom having achieved Hb improvement at month 12. Conclusion: After 3 months of treatment, deferasirox had no impact on transfusion requirement in regularly transfused patients with low‐risk MDS. However, deferasirox could induce 31% of erythroid response during the 12‐month follow‐up period thus suggesting that iron chelation therapy with deferasirox may induce an effect on hematopoiesis in a subset of patients with MDS and iron overload.